Hannibal ad portas: predicting the potential distribution of the exotic wood decay fungus Coniophora olivacea, new in Patagonia - Fernando Moro Cordobés; Paola Almonacid; Oscar Troncoso; Gonzalo Romano; Francisco Kuhar (Lilloa, 2023)
Coniophora olivacea has been traditionally considered as an important decay agent of building timbers of broadleaf and conifer woods, and causes significant damage on doors, window frames and other wood structures exposed to the environment. A more restricted role as tree pathogen has been also reported in cold climates. Studies of the predicted distribution of potentially invasive species are a useful tool to focus management efforts. Maximum-Entropy models allow predictions based on climatic and altitudinal layers as well as on previous data on the occurrence of species. The aim of this work is to report the presence of this wood decay fungus for the first time in Patagonia, and also to predict the potential spread pattern of this species using Maximum-Entropy.